Metal free, I2-catalyzed [3+1+1] cycloaddition reactions to synthesize 1, 2, 4-trisubstituted imidazoles. Issue 44 (28th October 2015) - Tang, Dong; Guo, Xin; Wang, Yu; Wang, Jing; Li, Jihui; Huang, Qiangwei; Chen, Baohua
Graphical abstract: We have successfully developed an operationally simple and economical one-pot three-component cycloaddition reaction to synthesize 1, 2, 4-trisubstituted imidazoles by employing aldehydes, α-amino carbonyl compounds and ammonium acetate. The transformation is environmentally friendly and metal free by employing I2 (10 mol %) as a catalyst and EtOH as a solvent, and a wide range of function groups and heterocyclics are well tolerated resulting in moderate to good yields. Abstract: We have successfully developed an operationally simple and economical one-pot three-component cycloaddition reaction to synthesize 1, 2, 4-trisubstituted imidazoles by employing aldehydes, α-amino carbonyl compounds and ammonium acetate. The transformation is environmentally friendly and metal free by employing I2 (10 mol %) as a catalyst and EtOH as a solvent, and a wide range of function groups and heterocyclics are well tolerated resulting in moderate to good yields.